1980
DOI: 10.1530/acta.0.0950350
|View full text |Cite
|
Sign up to set email alerts
|

Uptake of L-triiodothyronine into human cultured lymphocytes

Abstract: The cellular uptake of [125I]L-triiodothyronine and its analogues was investigated in IM-9 human cultured lymphocytes. Uptake of L-triiodothyronine was one half maximal within 15 min of incubation and maximal within 45 min. The efflux of the hormone followed first order kinetics having a one half time of 15 min. Treating the cells with either the mitochondrial inhibitors antimycin-A and potassium cyanide, or lowering the incubation temperature to 12\s=deg\C, markedly reduced uptake. The uptake of [125I]L-triio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1983
1983
1993
1993

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…The possible role of the plasma membrane in regulating peripheral thyroid hormone metabolism has been extensively studied (1)(2)(3)(4)(5)(6)(7)(8)(9). A specific hormone uptake has been described in hepatocytes (6), erythrocytes (5), lymphocytes (4), pituicytes (8), and fibroblasts (9).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The possible role of the plasma membrane in regulating peripheral thyroid hormone metabolism has been extensively studied (1)(2)(3)(4)(5)(6)(7)(8)(9). A specific hormone uptake has been described in hepatocytes (6), erythrocytes (5), lymphocytes (4), pituicytes (8), and fibroblasts (9).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormone is an amino acid derivative, although apparently not sharing the A system (unpublished data). The (4,400 ,uCi/gg) were purchased from New England Nuclear (Boston, MA). The purity of labeled and unlabeled hormones was assayed by thin-layer chromatography on silica gel KIF (Whatman, Inc., Clifton, NJ) using the solvent system formic acid/methanol/chloroform (1:3:16), according to Sato and Cahnmann (14).…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid hormones (THs) must cross the target cell plasma membrane in order to reach their receptors and metabolizing sites. Several types of cells have specific systems for TH transport (Krenning et al, 1978;Holm et al, 1980;Cheng, 1983;Pontecorvi and Robbins, 1986;Osty et al, 1988). Some studies of metabolic blockers and TH uptake into isolated tissues or cells suggest that Na+ and ATP are involved in TH transport across the plasma membrane (Krenning et al, 1981(Krenning et al, , 1982Centani and Robbins, 1987).…”
mentioning
confidence: 99%
“…It was previously shown that the Km of the T3 transport system of rat hepatocytes showed a homoge¬ neous temperature dependence between 0 and 37°C (11,14). The medium was removed and transport exper¬ iments were started by the rapid addition of 0.3 ml…”
Section: Pre-equilibration Of Washed Erythrocytes With [123i]t3mentioning
confidence: 99%